2015
DOI: 10.12669/pjms.316.8445
|View full text |Cite
|
Sign up to set email alerts
|

Resistance patterns of Multidrug resistant Acinetobacter baumannii in an ICU of a tertiary care hospital, Malaysia

Abstract: Backgrounds & Objective:Antimicrobial resistance is a major health problem worldwide in hospitals. The main contributing factors are exposures to broad-spectrum antimicrobials and cross-infections. Understanding the extent and type of antimicrobial use in tertiary care hospitals will aid in developing national antimicrobial stewardship priorities.Methods:In this study, we have analyzed the antimicrobial agents’ usage for acquisition of multidrug resistant using retrospective, cross-sectional, single-centre stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
4
1
1
Order By: Relevance
“…Of 8 studies reporting LOS, 7 reported that total hospital or ICU LOS tended to be longer for patients with MDR infections. For example, Janahiraman et al 25 found that, on average, patients infected with MDR-AB stayed in the ICU for an additional 15.3 days, compared to 17.9 days for those without MDR-AB. Importantly, not all studies performed statistical adjustments to minimize potential confounders between groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 8 studies reporting LOS, 7 reported that total hospital or ICU LOS tended to be longer for patients with MDR infections. For example, Janahiraman et al 25 found that, on average, patients infected with MDR-AB stayed in the ICU for an additional 15.3 days, compared to 17.9 days for those without MDR-AB. Importantly, not all studies performed statistical adjustments to minimize potential confounders between groups.…”
Section: Resultsmentioning
confidence: 99%
“…Our study has some limitations. First, LOS comparisons should be interpreted with caution because not all studies 25 , 40 performed statistical adjustments to eliminate confounder bias. Second, data regarding types of infection are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the number of deaths attributable to antimicrobial resistance is projected to be 10 million annually by 2050 2. In addition, antimicrobial resistance has been associated with high mortality, substantial healthcare expenditure and prolonged hospital stay worldwide, including Malaysia (a developing country) 1–3…”
Section: Introductionmentioning
confidence: 99%
“…Spostrzeżenia te pokrywają się z danymi z piśmiennictwa, które wskazują, że u chorych z grup ryzyka, m.in. : poprzednio hospitalizowanych, poddanych wcześniejszej antybiotykoterapii [8], zabiegom operacyjnym, w podeszłym wieku, z przewlekłymi chorobami układu oddechowego, z chorobami układu krążenia, chorobami metabolicznymi, niewydolnością nerek, wątroby, występuje częstsze ryzyko izolacji drobnoustrojów lekoopornych [12,13], a poziom występowania zgonów sięga 61% [5] lub nawet 70% [4]. W niniejszej pracy ustalono, że zastosowane leczenie empiryczne chorych z VAP różniło się od zalecanych rekomendacji.…”
Section: Dyskusjaunclassified